The Impact of Matchmaking on Family Harmony from the Perspective of Islamic Law: A Case Study in Klampar Village, Proppo District, Pamekasan Regency - Nuris Sadad; Jamiliya Susantin (Dinasti Research, 2026)
This study examines the impact of matchmaking on family harmony from the perspective of Islamic law in Klampar Village, Proppo District, Pamekasan Regency. Matchmaking practices remain strongly maintained as hereditary traditions within Madurese society and are closely related to the preservation of lineage, kinship, and family honor. However, these practices often create tensions between cultural traditions and individual rights in determining marriage partners. This research aims to analyze the persistence of matchmaking traditions, their impact on household harmony, and the perspective of Islamic law regarding arranged marriages. The study employs an empirical legal research method with a qualitative approach. Data were collected through in-depth interviews, observation, and documentation involving married couples, parents, religious leaders, and community figures in Klampar Village. The findings reveal that matchmaking practices continue to be preserved because they are considered capable of maintaining family relationships and social values. Nevertheless, excessive parental intervention, lack of emotional readiness, and limited acquaintance before marriage frequently contribute to household conflict and disharmony. On the other hand, some couples successfully maintain harmonious relationships through adaptation, communication, religious commitment, and family support. From the perspective of Islamic law, matchmaking is permissible as long as it is conducted based on mutual willingness and without coercion. Therefore, achieving harmonious family relationships requires balancing cultural traditions with the individual rights emphasized in Islamic teachings.